Autoimmune Hypophysitis With Systemic Lupus Erythematosus: A Case Report and Literature Review - Xiang, Pengyue; Wu, Qiuxia; Zhang, Hua; Luo, Chaoyang; Zou, Huajie (Frontiers in Endocrinology, 2020)
Background: Autoimmune hypophysitis (AH) is a primary autoimmune inflammatory disorder of the pituitary gland, which usually presents as a mass in the sella turcica. Systemic lupus erythematosus (SLE) is another inflammatory disorder in which the immune system attacks healthy cells and tissues throughout the body. Although both diseases are autoimmune disorders, they rarely coexist, and the relationship between them is unclear. Case Report: A 66-year-old man was evaluated at the endocrinology clinic because of worsening fatigue, anorexia, drowsiness and leg oedema. Examination revealed alertness impairment and lower limb oedema. Laboratory tests showed anterior pituitary hypofunction. The treatment approach, with glucocorticoids and immunosuppressive agents, resulted in long-term remission of symptoms of hypopituitarism and hyponatraemia. Conclusions: Our case demonstrates a potential association between AH and SLE. AH may need to be considered in the evaluation of SLE patients with headache, hyperprolactinemia, a pituitary mass, and hypopituitarism.